Pengaruh Promosi dan Kualitas Pelayanan Terhadap Kepuasan Konsumen pada Biro Perjalanan Rosalia Indah di Kediri - Ari Sandy Manuela; Nonni Yap; Sudjiono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aimto analyze the effect of promotion and service quality on customer satisfaction at Rosalia Indah Travel Agency. In the increasingly tight competition of the transportation business, promotion strategies and quality services are important factors in maintaining and increasing customer satisfaction. This study uses a quantitative approach with a survey method. Data were obtained through questionnaires distributed to 100 respondents who had used Rosalia Indah services. The analysis technique used was multiple linear regression to determine the effect of each independent variable (promotion and service quality) on the dependent variable (customer satisfaction). The results showed that promotion and service quality had a positive and significant effect on customer satisfaction, both partially and simultaneously. Among the two variables, service quality had the most dominant effect. The coefficient of determination (R²) of 0.65 indicates that 65% of the variation in customer satisfaction can be explained by promotion and service quality.